The Central Council for the Care of Cripples : What it is, and what it does
1933-12 1933 1930s 4 pages in orthopaedic work, and for a number of orthopaedic clinics covering the area served by each hospital. Clinics are particularly important for the examination of children with a view to discovering potential cripples at the earliest possible age, for treating those who do not need to go to hospital, and for the after-care of those who have completed hospital treatment. To enable those who must still remain cripples to become at any rate partly self-supporting and so to live far happier lives, there is an urgent need for many more workshops where these cripples can obtain vocational training in such employments as they are able to take up, and also a smaller number of special workshops or colonies for the permanent employment of those cripples whose disabilities will never allow them to compete in the industrial market. HOW THESE NEEDS CAN BE SUPPLIED. The Central Council believes that the cripples problem can only be satisfactorily and economically solved on a national scale by a scheme under which the whole country is divided into suitable areas, and by the establishment in each area of a central orthopaedic hospital together with a group of associated orthopaedic clinics, and facilities for providing vocational training. In furtherance of this national scheme the Central Council endeavours to organise the formation of a Local Association for the Care of Cripples in each area to help in carrying such local schemes into effect and to promote the general welfare of all the cripples and potential cripples in its area. It is, of course, essential that every local scheme should secure the goodwill and co-operation of the local Public Authorities for Health and Education. A leaflet setting out in detail the duties of a Local Association and its relation to the Public Authorities and the clinics in its area, has been prepared by the Council and can be obtained from the Secretary. 292/841.51/2/4